Experiencing Loneliness in Motherhood - Damba Bestari; Anish V. Cherian (Jurnal Psikiatri Surabaya, 2024)
Introduction: Motherhood is a lifelong learning process. Becoming a mother involves huge changes and a major shift in identity. We usually don’t pair loneliness with motherhood, but researchers have found that motherhood could be filled with lonely feelings. A study by the British Red Cross found that more than 83% of mothers under 30 years old feel lonely at some time. Even before COVID, one study found that more than 90 percent of moms reported feeling lonely after having kids, over one-third said they cried regularly, and more than half suffered from anxiety. This study aims to determine the problems with loneliness in motherhood and how they influence the whole family’s long-term growth and wellness. Methods: PubMed and Google Scholar were searched using the following keyword: (loneliness) AND (motherhood) AND (mental health) AND (maternal) using the journal publication filter for the 2018-2023 issue. Review: Loneliness isn’t only a concern for mothers but also for all family members. Mothers who experience a high degree of loneliness are likely to be depressed, which in turn leads to decreased self-esteem and poor health, and consequently the poor health of their children. Stronger involvement of the mother’s family, friends, and other support systems should be promoted. Conclusions: Researchers should pay attention to the facts that building close connections with others can stop social isolation in mothers from taking a toll on their mental health Keywords: Loneliness, Motherhood, Mental Health, Maternal